General precautions and safety aspects of facial laser treatment - Heppt, Werner; Metelmann, Hans-Robert; Heppt, Markus; Feller, Gabriele; Vent, Julia (Facial plastic surgery, 2018)
The current overview of laser radiation therapy options and the legal aspects of the head and neck region provides insight into the available laser hardware, discusses the indications and treatment options and risks, as well as the necessary precautions to be taken when operating a laser device. Further handling recommendations and requirements for the laser devices are drawn and the question of transferring tasks to nonmedical personnel is discussed. The reader should get an idea about the benefits and risks of using lasers in treating patients and be able to set the precise indication on the background of possibilities, adverse effects, and legal aspects.